Three – Mirror Laser Design to Calculate some Plasma Parameters - Rahim, Dilshad O. H. (Sulaimani Journal for Pure and Applied Sciences, 2001)
In this project, a new design have been suggested to use three r mirror laser as an interferometer by coupling a laser cavity with on other passive one containing low density cold plasma The aim of coupling is to study some important parameters of the plasma via a simply gained broadening technique. The parameters in question are the plasma refractive index (u), and the electron concentration 01.). The design was appearing to he successful when some numerical calculations 'were held and compared to previous experimental works
Keywords: Atomicand molecular collision; plank and laser physics Enerquhestribution function